A Study on Frontal Deformation of Lightweight Vehicle Due to Different Load Impact - ibrahim, mohd norihan; mohd zafir, mohamad zafrul hafizi (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The application of finite element models in the development and evaluation of the performance of lightweight vehicle at varying impact force. The study’s analysis permits the determination of the frontal area deformation of a lightweight vehicle impact test with different force. The vehicle’s force is split into five distinct categories: lowest, low, medium, high and highest. Due to considerable advancements in computer technology and nonlinear finite element software, the outcome of a complex accident involving a lightweight vehicle impact test and can be accurately anticipated using SOLIDWORK simulation software. The impact test at 500N force is 2.31e + 07 N/m2, 6.94 + 07 N/m2 m at 1500N force, 1.16 + 08 N/m2 at 2500N force, 1.62e+ 08 N/m2 at 3500N force and 2.08e+ 08 N/m2 at 4500N force. Due to the material properties of plain carbon steel, a lightweight vehicle can absorb more impact energy.